The technical optimization of Na-K lidar and to measure mesospheric Na and K over Brazil. (January 2021) - Du, Lifang; Jiao, Jing; Li, Faquan; Lin, Xin; Liu, Zhengkuan; Batista, P.P.; Pimenta, A.A.; Andrioli, V.F.; Wang, Jihong; Chen, Xuewu; Xia, Yuan; Wu, Fuju; et al.
Highlights: This paper reported that a Na-K lidar was built at 2016 at são josé dos Compose, Brazil, by the joint work of NSSC and INPE. This system realized the potassium and sodium metal layer at the simultaneously observe in Brazil, and this is the first time of potassium layer detection in South America. The original echo photon count of potassium layer is about 1633 (200 s, 96 m) and the signal-to-noise ratio is up to 40:1. Compared with the available detection results of Germany reported that using all-solid-state laser system detection potassium layer obtained 357 photons (1 min, 100 m), and the Na-K lidar observe in Brazil obtained 450 photons with the same resolution.The detection capability of potassium lidar has reached the leading position. The simultaneous phenomena of Nas and Ks, and a ultra-high density K layers have been observed, the K density in these narrow layers exceeds 1019 cm −3 . Abstract: This paper reports that the sodium–potassium (Na–K) lidar was completed in November 2016 at São José Dos Compose, Brazil (23°S, 45°W), by the joint effort of the National Space Science Center, Chinese Academy of Sciences (NSSC) and Instituto Nacional de Pesquisas Espaciais (INPE). This system realized the Na and K metal layers simultaneously observe in Brazil, and this is the first instance of K layer detection in South America. Some of the key parameters and technologies have been optimized based on the Na and K layer dual-wave lidar in Beijing Yanqing station, such as improve technical parameters for receiving telescope, the narrow linewidth, efficient laser frequency doubling, the wavelength automatic locking techniques. By adopting these technologies, the output were 589 nm and 770 nm lasers, with high emission powers of 75 mJ and 83 mJ, respectively, and backscattered signals of Na and K layers with high signal quality were obtained. Observation data showed that the original echo photon count of the Na layer was approximately 42, 486 (time resolution: 200 s, spatial resolution: 96 m) and the number of noise photons was 286 in a single data acquisition. The signal-to-noise ratio was up to 205:1. At the same spatiotemporal resolution, the original echo photon count of the K layer was approximately 1633, the noise photons were 38, and the signal-to-noise ratio was up to 40:1. The initial photocounts received has demonstrated that the Brazil K lidar has produced high quality signal with signal-to-noise level required by intended science studies. Moreover, the simultaneous phenomena of sporadic Na (Nas) and sporadic K (Ks), and the highly concentrated layers of atomic K have been observed, the K density in these narrow layers exceeds 1019 cm −3 .